The Compressive Strength of Unfired Clay Brick with MICP Reinforcement - Ochtharima, Zaerima Zahira; Indriani, Andi Marini; Utomo, Gunaedy; Maslina, Maslina (Universitas Negeri Padang, 2024)
Industrial waste in the form of sewage sludge, which is often overlooked, can have significant environmental impacts, especially polluting groundwater and surface water sources. This pollution leads to degradation of water quality, reduces the availability of clean water, and affects ecosystems. To reduce these impacts, sewage sludge can be utilized in the manufacture of construction materials, such as bricks, which is considered an economical and environmentally friendly solution. Fireless brick making, in accordance with the concept of green building, avoids air pollution from the firing process. This study explores the use of Bacillus huizhouensis bacteria in the Microbially Induced Calcite Precipitation (MICP) method to improve the strength of fireless bricks. Bacillus huizhouensis, which can hydrolyze urea and produce calcium carbonate (CaCO₃) or calcite, was chosen for its ability to produce CaCO₃ under alkaline conditions. Bacillus Huizhouensis bacteria were used to strengthen bricks with 15%, 20%, and 25% bacteria concentration variations with culture ages of 8 hours, 10 hours, and 15 hours. The results showed that the addition of 15% sewage sludge and 25% Bacillus huizhouensis bacterial solution with a culture age of 10 hours produced the highest compressive strength of 34.20 Kg/cm² (3.35 MPa), compared to sewage sludge bricks without bacteria (13.87 Kg/cm² or 1.36 MPa). Although showing significant improvement, this value is still below the SNI 15-2094-2000 standard of 50 Kg/cm² (5 MPa).